Clinical Profile and Endoscopic Findings in Patients undergoing Colonoscopy at a Tertiary Care Centre of Western Nepal - Bhattarai, Subash; Acharya, Ramesh Raj (Journal of College of Medical Sciences-Nepal, 2020)
Background: Colonoscopy is an invasive procedure used for both diagnostic and therapeutic purpose for detection and management of the diseases of rectum, colon, and terminal ileum. This study was undertaken to assess the clinical profile and endoscopic findings in patients undergoing colonoscopy. Methods: One hundred and sixty patients underwent colonoscopy from January 2018 till December 2019. Clinical profile, endoscopy and histological findings were studied from the hospital departmental records. Results: The commonest indications for performing colonoscopy were chronic diarrhea, altered bowel habits, chronic abdominal pain and bleeding per rectum. Colitis of unspecified etiology followed by ulcerative colitis and polyps were the common colonoscopy findings. Colorectal carcinoma were not uncommon. Conclusions: Colonoscopy is the gold standard modality for diagnosis of pathologies of lower gastro intestinal tract and should be an integral part of management. Screening colonoscopy is strongly recommended. Keywords: colitis; colonoscopy; colorectal disease